The Application of Virtual Simulations using Second Life in a Foreign Language Classroom - Tecnam Yoon (Journal of Education and Learning (EduLearn), 2014)
The purpose of this paper is to investigate the effects of virtual simulation-based language learning in a foreign language class in Korea. Total 35 1st-year university students in Korea participated in this research to figure out the effect of simulations. A virtual English learning community, ‘Cypris Chat’ in Second Life was selected as a learning tool. For the data collection, a survey questionnaire was distributed and analysed quantitatively. The result shows that the majority of the students had a positive attitude toward using a virtual simulation in English learning and had better understanding in learning English by experiencing an authentic practice. The first section of this paper provides a general overview of simulations in educational settings through an insightful literature review of the current research in the area. The review includes a comprehensive outlook on simulations, an example of successful classroom integration and some of the considerations researchers have found for their implementation. The latter section addresses the research method, results and conclusions.